Hypercalcemia and co-occurring TBX1 mutation in Glycogen Storage Disease Type Ib: case report - Zakaria Kasmi; Imane Ain El Hayat; Zahra Aadam; Abderrahmane Errami; Ibtihal Benhsaien; Jalila EL Bakkouri; Dalal Ben Sabbahia; Meryem Atrassi; Ahmed Aziz Bousfiha; Fatima Ailal (BMC Medical Genomics)
Abstract Glycogen Storage Disease Type Ib (GSD-Ib) is a rare autosomal recessive metabolic disorder caused by mutations in SLC37A4, leading to a deficiency in glucose-6-phosphate translocase. This disorder is characterized by impaired glycogenolysis and gluconeogenesis, resulting in clinical and metabolic manifestations. We report a three-month-old Moroccan female patient presenting with doll-like facies, hepatomegaly, dysmorphic features, and developmental delays. Laboratory analysis revealed hypoglycemia, elevated triglyceride levels, hypercalcemia, and neutropenia. Genetic testing confirmed a homozygous pathogenic variant in SLC37A4 and a heterozygous variant of uncertain significance in TBX1. Initial management included a lactose-free and galactose-free diet, multivitamin supplementation, and granulocyte colony-stimulating factor (G-CSF) therapy to address neutropenia. A novel aspect of this case involves hypercalcemia as an unusual finding in GSD-Ib and the co-occurrence of a variant in the TBX1 gene, which is not typically associated with the disease but may contribute to the patient’s clinical presentation. These findings add a new dimension to our understanding of GSD-Ib and suggest potential avenues for future research to elucidate these genetic interactions and their impact on clinical outcomes.